3D hydrodynamical survey of the impact of a companion on the morphology and dynamics of AGB outflows. Issue Volume 16:Issue S366(2020) (November 2020) - Malfait, Jolien; Maes, Silke; Homan, Ward; Bolte, Jan; Siess, Lionel; De Ceuster, Frederik; Decin, Leen
Abstract: With the use of high-resolution ALMA observations, complex structures that resemble those observed in post-AGB stars and planetary nebulae are detected in the circumstellar envelopes of low-mass evolved stars. These deviations from spherical symmetry are believed to be caused primarily by the interaction with a companion star or planet. With the use of three-dimensional hydrodynamic simulations, we study the impact of a binary companion on the wind morphology and dynamics of an AGB outflow. We classifiy the wind structures and morphology that form in these simulations with the use of a classification parameter, constructed with characteristic parameters of the binary configuration. Finally we conclude that the companion alters the wind expansion velocity through the slingshot mechanism, if it is massive enough.